Hydraulic conductivity and undrained shear strength of clay-construction and demolition solid waste materials mixtures - Abdulnafaa, Mohammed; Awad, Muwafaq; Cabalar, Ali; Akbulut, Nurullah; Ozufacik, Burak (Associacao Brasileira de Mecanica dos Solos, 2021)
The study aims to investigate the effects of three different construction and demolition materials (CDMs), including crushed waste asphalt (CWA), crushed waste bricks (CWB), and crushed waste concrete (CWC), on some geotechnical properties of low plastic clayey soil, particularly, the undrained shear strength (Su ) and the hydraulic conductivity (k). A set of experimental tests were performed on clayey soil and on clayey soil-CDM mixtures at mixing ratios of 5%, 10%, 15%, and 20% by dry weight. The results show that the soil plasticity decreases as the CDMs increase. Quantitatively, it is found a maximum of 12%, 6%, and 6% decrease in the liquid limits (LL) and a maximum of 9%, 4%, and 6% decrease in the plasticity limit (PI) of the mixtures with 20% of CWA, CWB, and CWC, respectively. The results of the Su estimated empirically from the fall cone tests show that the Su decreases as the CDMs increase. The Su reduces by approximately 10% and 2% of the mixtures with 20% CWA and CWB, respectively. But the Su is not affected by the CWC additive for water content lower than approximately 35%. The k value increases as the CDMs increase. The results show that the reported k value increases by 75%, 79%, and 247% of the mixtures with 20% of CWA, CWB, and CWC, respectively. Additionally, the k values obtained from the consolidation test confirm the findings of the effect of the CDMs on the coefficient of hydraulic conductivity. © 2021, Associacao Brasileira de Mecanica dos Solos. All rights reserved.
Keywords: clay; construction and demolition; hydraulic conductivity; material; undrained shear strength